A laparoscopic technique for in vivo observation of ovaries in the water buffalo (Bubalus bubalis) - Jainudeen, Mohamed Razeen; Bongso, T. A.; Ahmad, F. Bashir; Sharifuddin, W. (BMJ Publishing Group, 1982)
A technique was developed for observing the ovaries of the water buffalo (Bubalus bubalis) restrained in a standing position using a laparoscope (10 mm diameter, 600 mm length) inserted in the right paralumbar fossa after sedation with xylazine and local infiltration anaesthesia. Insufflation of the abdominal cavity with carbon dioxide was necessary to pass the laparoscope along the body wall to the pelvic inlet where both ovaries could be examined in detail with a manipulating probe inserted ipsilaterally. Twenty-one buffaloes were subjected to 50 laparoscopic examinations without infections or adverse reactions. Laparoscopy was a simple, reliable and rapid technique for repeated observation of the ovaries in the buffalo